(untitled) (International Association of Biologicals and Computational Digest, 2023)
Luffa acutangula and Luffa cylindrica are popular vines belonging to the Cucurbitaceae family. They are extensively used as vegetables across the globe. Cucurbitaceae plants have played a major role in Indian medicinal systems and ethnopharmacology. Various plant parts have pharmacological properties viz. antioxidant, antiinflammation, antidiarrheal, anticancer, antiulcer and so on. These properties are due to phytochemicals present in the plants. Phytochemistry is the study of plant chemicals, particularly secondary metabolites. These metabolites are typically produced as a self-defence mechanism against insects, pests, pathogens, herbivores, ultraviolet exposure, and environmental hazards. The present study is aimed to identify and quantify certain phytochemicals which are known to be responsible for bioactivities. Peels are generally thrown away in culinary practice, but they are highly rich in phytochemicals. Peels of both plants have taken for the study and qualitative analysis of phytochemicals such as alkaloids, phenols, flavonoids, sterols, tannins, saponins, etc. were carried out. Plant extracts of different solvents were compared for antioxidant potential as well as total phenols and total flavonoids. Quantification of phenols and flavonoids was carried out as they are reported to have antioxidant potential. FRAP assay was performed to check the capacity of plant extract to scavenge free radicals. The correlation of phenols and flavonoids was carried out with antioxidant results to establish the fact. The plant extracts’ total phenolic content was 66-357 mg gallic acid equivalent. The highest flavonoid content was found in methanol extracts of L. acutangula and L. cylindrica with values of 133.450 and 126.132 mg quercetin equivalent. FRAP assay concluded that methanol extracts of both plants have highest reducing power. TPC and TFC have shown strong positive correlation with FRAP assay. The phytochemicals and antioxidant potential of L. acutangula and L. cylindrica state that they possess valuable nutraceuticals. The pharmacological potential of the plants should be explored to maximum potential.